Spatial Justice and the City of São Paulo - Wagner, Cynthia (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2012)
As Brazil is one of the economically uprising and promising BRIC countries, its development involves chances and risks. If unjust conditions remain, its long-term advancement is rather unlikely. The changes within the country are especially visible and present in its principal metropolis: São Paulo. In order to analyze its present situation in terms of spatially produced social (in)justices, some questions must be answered: How is spatial justice produced and by which processes? How are those processes integrated in Brazil’s urbanization development? Which effects does it have on the urban structure of São Paulo? And finally: Which socio-spatial development tendencies do the actual public policies and their realization within the metropolis suggest? This bachelor thesis outlines a theoretical base of the term spatial justice, the development of Brazil - and in this context the effects on São Paulo’s urbanization - with respect to its economy, politics, society, history, and especially urbanization in order to analyze São Paulo’s socio-spatial development and present situation in a multidimensional context. Applying Henri Lefèbvre’s, David Harvey’s, and Edward Soja’s theories on spatial justice on the public policies of the metropolis since the City Statute of 2001 – a major change in Brazil’s urban politics –, the author looks into their conformance with the necessary production conditions of spaces of justice.
Keywords: Gerechtigkeit; São Paulo; Städtebau; Brasilien; 910 Geografie, Reisen